If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -12 = x + 6 Reorder the terms: -12 + 4x = x + 6 Reorder the terms: -12 + 4x = 6 + x Solving -12 + 4x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + 4x + -1x = 6 + x + -1x Combine like terms: 4x + -1x = 3x -12 + 3x = 6 + x + -1x Combine like terms: x + -1x = 0 -12 + 3x = 6 + 0 -12 + 3x = 6 Add '12' to each side of the equation. -12 + 12 + 3x = 6 + 12 Combine like terms: -12 + 12 = 0 0 + 3x = 6 + 12 3x = 6 + 12 Combine like terms: 6 + 12 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| 5b*6b= | | 3x*5x*2x= | | 6(2z-1)-2(z+3)=3(z+1) | | 20y-10=10 | | 3a*4a= | | b/14=5/10 | | X+(-4)+2x=14 | | 9-10x=77-38x | | -18x^2+65x+7=0 | | 3x^3-7x^2=-10 | | 9d-2d+6d-6=6d | | y/8=2/10 | | (3+5x^2)(3-5x^2)= | | 3x^3-7x^2=10 | | 9x-7=6x+16 | | (2x+3)2-3x-4=0 | | 16a^3b+4ab=0 | | 6+9+6= | | 12X^3+3X^2-24X^2-6X=0 | | (x+2)(x+8)=72 | | 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 | | (3d^4-4d^3+6)(-3cd)= | | 4(6X-5)2= | | 6d+3d-5d-8=2d | | 9n=8n+24 | | 3x-9=2x+15 | | 5(3x-2)5= | | 3n+10=70 | | 12n-3=9 |